Measuring fuel poverty: General considerations and application to German household data - Peter Heindl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Fuel poverty may become an increasingly severe problem in developed countries in cases when real prices for fossil fuels increase at high rates or when real energy prices increase due to policies for greenhouse gas abatement. Fuel poverty measurement consists of two largely independent parts, firstly, the definition of an adequate fuel poverty line, and secondly, the application of techniques to measure fuel poverty given some poverty line. This paper reviews options for the definition of fuel poverty lines as well as techniques for fuel poverty measurement. Based on household data from Germany, figures that would result from different fuel poverty lines are derived. Different fuel poverty lines partly yield highly different results with respect to which households are identified as fuel poor. Thus, the choice of the fuel poverty line matters decisively for the resulting fuel poverty assessment. Options for fuel poverty measurement and subgroup comparison in order to identify most vulnerable types of households are discussed in the light of the literature and based on applications to German household data.
Keywords: I32; Q28; Q48; 330; Fuel Poverty; Energy Poverty; Poverty Measurement; Energiearmut